Incidence of ocular toxicity from iron chelating agents at Siriraj Hospital - Atiporn Thuangtong (2020)
© 2020, Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: To determine the incidences of ocular toxicity and ocular findings, including structural and functional abnormalities, caused by iron chelating agents and detected by an electrophysiologic test at Siriraj Hospital. Methods: A retrospective chart review was conducted of patients receiving multiple blood transfusions and iron chelation therapy who had an eye examination at Siriraj Hospital between January 1995 and December 2017. Results: Ninety-seven charts were reviewed. The 88 patients included comprised 41 males and 47 females. Their ages ranged from 1 year 11 months to 47 years, with children predominant (mean: 8.13 years). Beta thalassemia HbE was the main diagnosis (87.5%). After receiving iron chelating agents, 3 patients had abnormal eye findings with suspected ocular toxicity. Two had retinal pigmentary changes, but only one of those two displayed a mildly decreased response in a scotopic electroretinogram. Although the third patient also showed a decreased electroretinogram response, there were no obvious retinal changes. All three received the iron chelating agents desferrioxamine, deferiprone, and/or deferasirox at different doses and for various durations. Conclusion: Although some pigmentary retinopathy and decreased electroretinogram responses were found, leading to ocular toxicity being suspected, there was a very low incidence of ocular toxicity from the chelating agents. In addition, the dosages of the agents causing ocular toxicity, and the duration of that toxicity, were inconclusive. Moreover, a gold standard for identifying ocular toxicity caused by chelating agents was not able to be established. Consequently, the risks and benefits of employing eye screening coupled with an invasive procedure like an electrophysiologic test will need to be weighed, especially with pediatric patients.